The textile design experimentation as representation and resignification of women in the post-conflict in Colombia - Martínez, Vanessa (Universidad de Boyacá, 2020)
After the signing of the Peace Agreements, the re-socialization of ex-combatants and victims of the war is one of the main challenges of the post-conflict in Colombia, where different components include an integral reincorporation into society are addressed. In this context, this article is presented as a reflection on the research-creation project in design called “My story has not ended yet”, proposed as a platform for social re-integration and re-signification of women through workshops and living design and reflection laboratories on textiles, embroidery and weaving under the principles of collaboration and co-creation. It was developed in 2018 in Bogotá, Colombia, as a design perspective with a social approach through a creation workshop based on the testimonial conceptualization of violence, the body, truth and its symbolic value to re-signify the subjects, which translated into design workshops for social hygiene and into the construction of social fabrics. From this experience a collection of clothing was obtained as a representation of women, as well as an exhibition of art-tissue exploration and a group of women empowered in their social fabric.